Evaluation of the feasibility of an Education‐Career pathway in Healthcare for Older People (ECHO) for early career nurses. (19th January 2023) - Naughton, Corina; Hayes, Nicky; Ezhova, Ivanka; Fitzpatrick, Joanne M.
Abstract: Background: Rapid population ageing is driving demand for qualified gerontological nurses. Yet, early career nurse attrition and limited focus on retention in the speciality limits supply. Objectives: To test the feasibility and acceptability of an Education‐Career pathway in Healthcare for Older People (ECHO) intervention for early career nurses to improve retention and capability in gerontological nursing. ECHO is a multicomponent intervention with integrated education, career planning and coaching components, tested over two 6‐month cycles. Methods: A feasibility study with a pre‐post design using a multi‐methods evaluation. Twenty‐nine early career nurse participants were recruited from eight NHS acute and community care Trusts in England. ECHO participants completed online questionnaires at baseline (Time 1), 6‐month (T2, end of intervention) and follow‐up at 18 months from baseline (T3). Outcome measures were career intention, self‐reported knowledge, career planning confidence, and burnout using the Maslach Burnout Inventory. Qualitative interviews were undertaken with participants ( n  = 23) and organizational stakeholders ( n  = 16) who facilitated ECHO. Data analysis used descriptive statistics and non‐parametric tests for paired data and thematic analysis for qualitative data. Results: Overall, 19 of 29 participants (65%) completed all aspects of the intervention. The evaluation was completed by 23 participants. ECHO was well received by participants and stakeholders. At T3, the 23 participants were working in the speciality, though two had changed organizations. There was a significant improvement in self‐reported gerontological knowledge, pre 87 (IQR 81–102), post 107 (IQR 98–112) p  = 0.006, but no significant changes in other outcomes. In qualitative data, participants and organizational stakeholders held similar views, presented under four main themes: intended outcomes (personal and professional development, raise gerontological profile, expand horizons); nurse retention‐a double‐edged sword, ECHO logistics, and sustainability. Conclusion: Education‐Career pathway in Healthcare for Older People was feasible and may positively impact early career nurse retention, capability and socialization into gerontological nursing. ECHO requires further refinement and piloting, but learning can contribute to retention strategies. Implications for practice: Attracting and retaining early‐career nurses to the gerontological speciality requires greater innovation, organizational and senior nurse leadership.